The effects of flosequinan on submaximal exercise in patients with chronic cardiac failure. - Elborn, J S (1990)
1. Twenty patients with moderate to severe chronic cardiac failure were entered into a double-blind parallel group study comparing flosequinan 100 mg daily with matching placebo. 2. After at least three prior exercise tests, cardiopulmonary parameters were assessed at rest and during submaximal exercise before and after 2 and 8 weeks of active drug or placebo. 3. Resting minute ventilation and respiratory rate were reduced by flosequinan compared with placebo, but oxygen uptake was unchanged. 4. Comparison of minute ventilation, carbon dioxide production and venous lactate levels at the end of the exercise stage approximating to 50% of peak oxygen uptake demonstrated significant reductions in the flosequinan group compared with placebo at week 2 and week 8 (P less than 0.05). 5. Flosequinan increased the oxygen uptake at anaerobic threshold from 13.2 +/- 2.8 ml min-1 kg-1 to 15.9 +/- 3.4 ml min-1 kg-1 at week 2 and 15.8 +/- 3.7 ml min-1 kg-1 at week 8. These increases were significant when compared with placebo (P less than 0.05). 6. We conclude that flosequinan improves submaximal exercise performance in patients with chronic cardiac failure, probably by enhancing skeletal muscle blood flow.